Move the sliders to change the values of h and k in the function g(x) = f(x - h) + k.

Describe in words the effects of h and k on the graph of y = g(x). I.e., explain the transformation that takes the graph of y = f(x) to the graph of y = g(x).
Now, double--click the f(x) function (in red) and change it to f(x) = sqrt(x). Observe what happens to g(x). Why is this? What are the effects of h and k on the graph of y = g(x)?
Double--click on f(x) and redefine it to another function of your choice. Observe what happens to g(x) and what the effects of h and k are on its graph.